ALIH AKSARA DAN ALIH BAHASA TEKS TASAWUF DAN TA’BIR GEMPA - Suryani, Lilis; Nurizzati, Nurizzati (Universitas Negeri Padang, 2019)
This research aimed to: (a) present a description of Tasawuf dan Ta’bir Gempa script, (b) present the transliteration form from Arabic-Malay into Latin script of Tasawuf dan Ta’bir Gempa text, (c) present the translation from Malay-Minang into Indonesian language of Tasawuf dan Ta’bir Gempa script. This research is a philology research. The object of his research is the text of theTasawuf dan Ta’bir Gempa. The method of this research is descriptive method and method of philology research which is adjusted with research stage. At the data collection stage, used field study method and literature study method and to library. The results of this research were (1) the complete description of the script, (2) the transcription ofTasawuf dan Ta’bir Gempatext from Arabic-Malay into Latin without changing the kind of language that can be read and understood by the present society(3) Tasawuf dan Ta’bir Gempa text had adapted into correct Indonesian Spelling (EBI). Some of Malay’s vocabularies and Minangkabau language’s vocabularies found inTasawuf dan Ta’bir Gempascript were maintained to preserve the purity of the old vocabulary.Keywords: philology, text, transliteration, translation